The Influence of Knowledge Level, Attitudes, and Socialization on Participation in the Social Security Administering Body (BPJS) in the Working Area of Bandar Jaya Public Health Center, Lahat Regency - Hermira Sandirka; Karnirius Harefa; Sri Melda Br. Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Active participation in BPJS is an important indicator of the successful implementation of the National Health Insurance (JKN) program. Although membership coverage is relatively high, inactive participants are still identified. This study aimed to analyze the influence of knowledge level, attitudes, and socialization on BPJS participation in the working area of Bandar Jaya Public Health Center, Lahat Regency.This study employed a quantitative approach with an analytical observational design and a cross-sectional method. The study population consisted of 9,400 household heads, with a sample of 97 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-Square test and multiple logistic regression at a significance level of 0.05.The results showed that knowledge level was significantly associated with BPJS participation (p = 0.002), attitudes were significantly associated with BPJS participation (p = 0.001), and socialization was significantly associated with BPJS participation (p = 0.000). Multivariate analysis revealed that socialization was the most dominant factor influencing active BPJS participation (OR = 5.12; 95% CI = 1.89–13.86; p = 0.001), followed by attitudes (OR = 4.38; p = 0.004) and knowledge level (OR = 3.96; p = 0.011).It can be concluded that knowledge level, attitudes, and socialization significantly influence BPJS participation, with socialization as the most dominant factor. Therefore, strengthening sustainable and community-based socialization strategies is necessary to increase active BPJS participation.